Does Military High-speed Boat Slamming Cause Severe Injuries and Disability?. Issue 11 (30th November 2022) - Ullman, Johan; Hengst, David; Carpenter, Ronald; Robinson, Yohan
Abstract: Background: Many operators of professional high-speed boats suffer severe, acute, and permanent injuries caused by slamming-induced hull impacts. As the number of professional high-speed boats and their speed capabilities increase, operators are reporting increasing numbers and severity of injuries. However, the actual incidence rate of acute injuries and the prevalence of chronic musculoskeletal disorders are still unknown. Questions/purposes: We sought to investigate, among professional high-speed boat operators, (1) the self-reported incidence rate of impact-induced injuries, (2) the most common types of injuries or injury locations, (3) what impact characteristics were reported, and (4) the prevalence of self-reported sick leave, disability, and medical or orthopaedic treatment. Methods: This study was an internet-based survey among retired military high-speed boat operators. The survey was given to members of the Combatant Craft Crewman Association online user group (360 members). Participants answered questions on demographics, service branch, service years and capacity, boat type, types of events, injury location, severity, pain, disability, and need for treatment. Values are presented as the mean ± SD and proportions. Incidence rates are presented as injuries per person-year. A total of 214 members of the Combatant Craft Crewman Association participated in the survey (213 men, mean age 50 ± 9 years, mean BMI 29 ± 4 kg/m 2 ). A total of 59% (214 of 360) of those we surveyed provided responses; all provided complete survey responses. Results: The self-reported incidence rate of impact-induced injuries was 1.1 injuries per person-year served onboard. A total of 32% (775 of 2460) of respondents reported injuries that affected the back, and 21% (509 of 2460) reported injuries that affected the neck. Among those who responded, 33% (70 of 214) reported loss of consciousness onboard, and 70% (149 of 214) reported having experienced impaired capacity to perform their job onboard because of impact exposure. A total of 49% (889 of 1827) of the reported injuries were attributed to impacts containing lateral forces, 18% (333 of 1827) to frontal impacts, and 12% (218 of 1827) were attributed to purely vertical impacts. Finally, 67% (144 of 214) of respondents reported at least one occasion of sick leave from training or missions. Seventy-two percent (155 of 214) applied for a Veterans Affairs disability rating, and 68% (105 of 155) of these had a rating of 50% or higher. Additionally, 39% (84 of 214) reported having had surgery during active duty, and 34% (72 of 214) reported surgery after leaving active service. Conclusion: The results suggest that in the investigated military population, exposure to slamming-induced impacts onboard high-speed boats may cause more injuries than previously reported. Most reported injuries are musculoskeletal, but the high number of reported slamming-induced events of unconsciousness is concerning. Level of Evidence: Level IV, prognostic study.